Using Classification and Regression Tree Analysis to Explore Parental Influenza Vaccine Decisions - Lama, Yuki (Vaccine, 2019)
BACKGROUND AND OBJECTIVES: Influenza poses a public health threat for children and adults. The CDC recommends annual influenza vaccination for children <18 years, yet vaccine uptake remains low for children (57.9%) and adults (37.1%). Given that parental decision-making is key in childhood vaccine uptake, there is a critical need to understand vaccine hesitancy among parents who decide not to vaccinate their children. This study aims to explore predictors of children’s influenza vaccine status given parental vaccination status and examine the factors that contribute to concordance or discordance between parental and children’s vaccine uptake. METHODS: Classification and regression tree (CART) analyses were used to identify drivers of parental decisions to vaccinate their children against influenza. Hierarchy and interactions of these variables in predicting children’s vaccination status were explored. RESULTS: From a nationally representative sample of non-Hispanic Black and White parents who completed an online survey (n=328), the main factors influencing parents’ decisions to vaccinate their children were vaccine behavior following physician recommendation, knowledge of influenza recommendations for children, influenza vaccine confidence and disease risk. Among unvaccinated parents, the greatest concordance was observed among parents who usually do not get vaccinated following physician recommendation and had lower knowledge of recommendations for influenza vaccination for children. The greatest discordance was observed among unvaccinated parents who had lower hesitancy about recommended vaccines. CONCLUSIONS: Understanding drivers of parental decisions to vaccinate themselves and their children can provide insights on health communication and provider approaches to increase influenza vaccine coverage and prevent influenza related mortality.